An Asian multi-national multi-institutional retrospective study comparing intracavitary versus the hybrid of intracavitary and interstitial brachytherapy for locally advanced uterine cervical carcinoma. (22nd April 2022) - Murakami, Naoya; Ando, Ken; Murata, Masumi; Murata, Kazutoshi; Ohno, Tatsuya; Aoshika, Tomomi; Kato, Shingo; Okonogi, Noriyuki; Saito, Anneyuko I; Kim, Joo-Young; Yoshioka, Yasuo; Sekii, Shuhei; et al.
Abstract: This study is an international multi-institutional retrospective study comparing the clinical outcomes between intracavitary brachytherapy (ICBT) and the hybrid of intracavitary and interstitial brachytherapy (HBT) for locally advanced cervical cancer patients treated with definitive radiation therapy. Locally advanced cervical cancer, the initial size of which is larger than 4 cm and treated by concurrent chemoradiotherapy and image-guided adaptive brachytherapy, were eligible for this retrospective study. Patients who received HBT at least once were included in the HBT group, and patients who received only ICBT were included in the ICBT group. Anonymized data from 469 patients from 13 institutions in Japan, one from Korea and one from Thailand, were analyzed. Two hundred eighty and 189 patients were included in the ICBT group and the HBT group, respectively. Patients in the HBT group had more advanced stage, non-Scc histopathology, a higher rate of uterine body involvement, larger tumor at diagnosis, larger tumor before brachytherapy and a lower tumor reduction ratio. With a median follow-up of 51.3 months (2.1–139.9 months), 4-y local control (LC), progression-free survival (PFS) and overall survival (OS) for the entire patient population were 88.2%, 64.2% and 83%, respectively. The HBT group received a higher HR-CTV D90 than that of the ICBT group (68.8 Gy vs 65.6 Gy, P  = 0.001). In multivariate analysis, the non-Scc histological subtype, HR-CTV D95  ≤ 60 Gy, reduction ratio ≤ 29% and total treatment time (TTT) ≥ 9 weeks were identified as the independent adverse prognostic factors for LC. Regarding LC, no difference was found between ICBT and HBT (4-y LC 89.3% vs 86.8%, P  = 0.314). After adjustment for confounding factors by propensity score matching, no advantage of applying HBT was demonstrated regarding LC, PFS, or OS. Despite the fact that HBT patients had more adverse clinical factors than ICBT patients, HBT delivered a higher dose to HR-CTV and resulted in comparable LC.